The Syriac Orthodox and Coptic Orthodox Churches in Austria: Inter-Church Relations and State Recognition - Andreas Schmoller (Mashriq & Mahjar, 2021)
This article explores the inter-church and church-state relations of the Syriac Orthodox and Coptic Orthodox Churches in Austria. The strong historic role of the Catholic Church in Austria's political landscape provides the central framework to understand the “story of success” regarding relations with both the Catholic Church and state authorities in Austria. Summarizing the history of migration and establishment of diaspora churches in Austria, the article explores the impact of the support of the Catholic Church in the process of institutionalization. In addition, state recognition and examples of church-state interaction are highlighted. The findings support the conclusion that minority churches from the Oriental Orthodox tradition have benefitted strongly from their relations with the majority church and the state. However, their authority in both religious and political contexts also affects personal leadership and internal affiliations which can lead to divisions within the church communities.